The effect of Gandasil and LB fertilizer concentrations on the growth of Dendrobium sp - Syarifah, Sharfina Mutia; Marsuni, Jenni Fer Try; Fardhani, Dinar Mindrati; Tryana, Elys (International Journal of Health Science and Technology, 2024)
Dendrobium sp. orchids, especially hybrid varieties, are one of the species that can tolerate direct sunlight well. Fertilizing these orchids involves using foliar fertilizers, made from organic or chemical materials, applied through the leaves' stomata. This method involves spraying the fertilizer to provide additional nutrients beyond what the roots absorb. This research aimed to determine the effects of fertilizers on leaf count and plant height. The experiment included two treatments and two replications, with methods such as media sterilization, sample preparation, watering, transplanting, fertilizing, and plant observation. Data were analyzed using one-way ANOVA with a p-value <0.05. Foliar fertilizer was applied to the underside of the leaves between 8-9 AM or 3-4 PM when stomata were open. Spraying was avoided during the rainy season to prevent fertilizer runoff while stomata were closed. Observations revealed that using Grow Quick Leaf Booster (LB) fertilizer at a concentration of 2 ml (diluted with ½ water) promoted longer growth than Gandasil fertilizer at 1 ml (diluted with ½ L of water and 1 tablespoon), which also produced good results and accelerated orchid growth. Gandasil increased plant height, leaf count, leaf diameter, and the number of seedlings, while LB fertilizer primarily enhanced plant height. These findings suggest that while both fertilizers improve growth, Gandasil has a broader range of benefits, including vegetative growth and leaf development, whereas LB is more focused on increasing plant height.